Wiedeńskie kontakty lwowskich bibliotekarzy. Z dziejów Austriackiego Stowarzyszenia Bibliotekarzy - Oxenius, Sławomir (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The Austrian Library Association (Österreichischer Verein für Bibliothekswesen) was one of the oldest associations of librarians in Europe, functioning in the years 1896-1919. Its goal was professional and scientific improvement as well as integration of librarians from different lands belonging to the Habsburg monarchy. The article presents the origin and activities undertaken by the Association, particularly the published periodical, which was thematically related to various aspects of working in libraries and the formation of the librarian profession. It also presented information about specific libraries (an address book of monarchy libraries was published). Lviv librarians who belonged to the Association actively participated in its operations: Rudolf Kotula published articles on, e.g., Polish libraries in Austria, especially the Library of the University of Lviv, as well as in other Polish communities. He also took part in an extraordinary congress in 1913, which revealed conflicts in the relationship between the Association’s headquarters and provincial librarians, as well as problems relating to the concept, financing and scope behind the periodical. This article uses source materials to date unknown in scientific communities.